Annotated Translation of William H. McRaven's Make Your Bed - Ellya Fuad Elsyahbani (Jurnal Linguistik Terapan, 2020)
This research is an Annotated Translation from English Into Indonesian of William H. McRaven’s Make Your Bed. The aims of this research are: (1) to identify the problems or difficulties during translating the book as the source text; (2) to find the solutions and solve the problems during translating the book as the source text. The methods used in this research are introspective and retrospective research methods. In this research, the researcher encountered 27 problems while translating the source text consisting of 7,300 words from English (source language) into Indonesian (target language) that are categorized into three categories namely understanding category, transferring category, and both understanding and transferring category. The problems were classified into word, phrase, and idiom problems. To solve the problems found in this research, the researcher utilized the Internet to search for information about the terms difficult to understand. Then the researcher used online dictionaries to find out the meaning of the difficult terms. The researcher also used translation strategies that were relevant and appropriate to solve the problems faced by the researcher. The strategies that were used by the researcher were literal translation, loan, borrowing, synonymy, unit shift, and idiomatic translation. This research can be used as a reference for future researchers who want to conduct an annotated translation research because this research contains of solutions that can applied to solve the problems faced during translation process.